An experimental study of the effect of nanoparticle additives to the refrigerant r141b on the pool boiling process - Khliyeva, Olga; Lukianova, Tetiana; Semenyuk, Yury; Zhelezny, Vitaly; Nikulin, Artem (Eastern-European Journal of Enterprise Technologies, 2018)
The results of the experimental study of the internal characteristics of the pool boiling process of the refrigerant R141b, solution R141b/surfactant Span-80 and nanofluid R141b/Span-80/ TiO2 nanoparticles on the surfaces of stainless steel and teflon have been presented. The measurement of the vapor bubble departure diameter, the vapor bubble departure frequency and the nucleation site density has been performed at atmospheric pressure and in the range of heat fluxes from 3.0 to 7.5 kW·m-2. The study showed that the vapor bubble departure diameter in nanofluid boiling on the stainless steel surface is 0.7 mm and on the teflon surface – 0.45 mm. Besides, the additives of nanoparticles to the solution of R141b/Span-80 lead to a decrease in the vapor bubble departure diameter in boiling on the teflone surfaces. The opposite effect was detected in boiling on the stainless steel surface. It is shown that the additives of TiO2 nanoparticles to the solution R141b/Span-80 lead to a decrease in the number of nucleation sites by 2–8 times. This effect depends on the heat flux and type of heaters surface. It was found that the rise of the heat flux leads to an increase in the difference between the magnitudes of nucleation site density for the teflon and stainless steel surfaces in boiling of R141b and R141b/Span-80. The number of nucleation sites on the teflon surface is 2 times lower compared with boiling on the stainless steel surface at a heat flux of 7.5 kW·m-2. The type of surfaces does not affect the number of nucleation sites and vapor bubble departure frequency in nanofluid boiling in the entire investigated range of heat fluxes. Based on the results of the study, it was found that the vapor bubble departure frequency in boiling of R141b and solution R141b/Span-80 on the teflon surface is 1.5–2 times lower compared with boiling on the stainless steel surface. The obtained experimental data can be used in predicting the heat transfer coefficient in boiling of the solution of R141b/Span-80 and nanofluid R141b/Span-80/TiO2.